Óleo de linhaça na dieta de fêmeas e machos castrados Nelore x Canchim, terminados em confinamento - Rosa, Bruna Laurindo [UNESP] (2014)
The objective was to evaluate the effect of diets containing levels of linseed oil in the performance, carcass characteristics, weight, yield of cuts of meat, and meat quality of heifers and steers Nellore x Canchim. Fifteen 24-monthold steers (427.80 ± 40.59 kg) and fourteen 24-month-old heifers (400.57 ± 32.57 kg, average body weight) were confined in individual pens, receiving diets with 80% of concentrated, sugar cane as exclusive roughage and increasing levels of linseed oil (1.0, 3.8 and 5.2% on a DM basis). The experiment was designed in an incomplete random blocks one, in a factorial scheme of 3 x 2 (type of diet and sexual condition). The initial weight of animals was used as co-variable and the blocks were considered as the randomizing effect. All of the animals of every block were slaughtered once they reached an average body weight of 500 kg; this resulted in 96 days of feedlot for two blocks, 110 days for other two blocks and 138 days for one block, after 28 days of adaptation. Dry matter consumption by animals, in kg and body weight percentage, was reduced (P<0.05), accompanied with higher daily weight gains, an improvement in feed efficiency and an increase in the Longissimus eye area in the carcass with an elevation of oil levels in diets, without differences between sex conditions. The backfat thickness increased with higher linseed oil levels on the diet and results differed between sex conditions, with higher values for heifers (12.17 mm) in relation to steers (8.58 mm). The weight of meat cuts such as the shoulder clod, complete top sirloin butt (top sirloin butt + top sirloin cap + bottom sirloin butt), strip loin and top round, as well as the sum of the noble meat cuts (top sirloin butt + strip loin + full tenderloin), less noble meat cuts (chuck roll + chuck mock tender + shoulder clod + fore shank and shank + hump + point half brisket + neck + outside round), barbecue ...